Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Cat Nippon Paint Wilayah Kota Semarang Pasca Pandemi Covid 19 - Alfin Muslikhun; Jayus Jayus; Khoerul Sholeh; Antin Azizah Ali; Rizkul Mubarok (Universitas Veteran Bangun Nusantara, 2022)
The aim of the research is to examine the influence of online promotion, brand image and product quality on the decision to purchase Nippon Paint paint in Semarang City following the Covid 19 Pandemic. The population in this research is all consumers in the Semarang City area. The sample that will be used in this research is 100 people selected using the purposive sampling method. The data analysis tool uses the SPSS application. Data testing uses data instrument tests, classical assumption tests, model feasibility tests, and multiple regression analysis tests. The results of testing hypothesis 1 (H1) show that online promotions have a significant positive effect on purchasing decisions. The results of testing hypothesis 2 (H2) show that brand image has a significant positive effect on purchasing decisions. The results of testing hypothesis 3 (H3) show that product quality has a significant positive effect on purchasing decisions. From the test results, it can be seen that the coefficient of determination (adjusted R2) obtained was 0.772. This means that the variables of online promotion, brand image and product quality can influence purchasing decisions by 77.2%. Meanwhile, the remaining 22.8% is influenced by other variables.